INVESTIGATION OF ASYNCHRONOUS OPTICAL COMMUNICATION CHANNEL THROUGHPUT CONTAINING A RECEIVER ON THE BASIS OF PHOTON COUNTER - I. R. Gulakov; A. O. Zenevich; A. M. Timofeev; A. G. Кosari (Приборы и методы измерений, 2015)
A mathematical model of asynchronous optical communication channel with a photon counter applied as a receiving module has been built. The expression for calculating of data throughput of this channel has been obtained. As a result of implemented experimental investigations it has been established that the data throughput of asynchronous optical communication channel containing a photon counter on the basis of avalanche photodetector as a receiving module depends on optical radiation and photodetector supply voltage.